Overview of User Experience in Using Nutrition Information System: Scoping Review - Putra, I Putu Okta Diwian Jaya; Purnami, Cahya Tri; Kartini, Apoina (Jurnal Multidisiplin Madani, 2024)
Manual nutrition record system which still have a few of limitation, was already developed into digital information system. The nutrition information system was implemented with the hope that officers can record and report data quickly, accurately and instantly. To determine the success of the information system implementation, an evaluation is necessary. This scoping review was conducted with the intention of obtaining an overview of the implementation of nutrition information systems in the last ten years to date. After screening using the PRISMA flow, 11 articles were obtained that were relevant to the criteria used to conduct the review. Article searches were conducted on four article search engines, namely Google Schoolar, JSTOR, PubMed, and Science Direct. Through these articles, found that the implementation of nutrition information systems has a few benefits and barriers. There are also several factors that influence this, although there are still several studies that have different results regarding the influence of these factors